Parabacteroides distinguishes bipolar disorder from schizophrenia: toward a microbial biomarker for differential diagnosis - Majie, Wang; Yifang, Hu; Yuncui, Huo; Yaping, Chen; Longhui, Li; Qianyan, Jin; Weiwei, Xie; Wei, Cui; Yucheng, Wang (Frontiers in Microbiology, 2026)
IntroductionSchizophrenia (SCZ) and bipolar disorder (BD) are severe psychiatric disorders with overlapping clinical manifestations and shared biological mechanisms. Growing evidence implicates the gut microbiota in neuroimmune and metabolic regulation, suggesting a potential role in the pathophysiology and heterogeneity of psychiatric disorders.MethodsIn this comparative study, fecal samples were collected from 43 patients with SCZ, 19 patients with BD, and 40 healthy controls (HC). Gut microbial composition was profiled using 16S rRNA gene sequencing. Microbial diversity, taxonomic composition, and predicted functional pathways were analyzed, and associations between key taxa and clinical symptom dimensions were assessed.ResultsBoth SCZ and BD patients exhibited significantly reduced microbial diversity and distinct alterations in gut microbial composition compared with HC. SCZ was characterized by a pro-inflammatory microbial profile, whereas BD showed dysbiosis associated with metabolic disturbances, particularly pathways related to lipid metabolism and obesity susceptibility. Functional prediction revealed downregulation of fatty acid biosynthesis and metabolism pathways, along with selective upregulation of antioxidant-related pathways in SCZ. Notably, Parabacteroides_B_862066 emerged as a major taxonomic feature distinguishing SCZ from BD. Its relative abundance was negatively correlated with hallucinations and attention impairment in SCZ, but positively associated with negative symptom domains in BD. Integration of Parabacteroides_B_862066 abundance with symptom scores demonstrated strong discriminative performance between SCZ and BD (AUC = 0.87).DiscussionThese findings suggest that Parabacteroides, particularly Parabacteroides_B_862066, may serve as a microbial indicator differentiating SCZ from BD. The distinct microbial and functional profiles observed between the two disorders highlight potential microbiota-related mechanisms underlying psychiatric heterogeneity and may provide insights into subtype-specific pathophysiology.